Childhood Infections, Antibiotics, and Resistance: What Are Parents Saying Now?. (February 2014) - Finkelstein, Jonathan A.; Dutta-Linn, Maya; Meyer, Robert; Goldman, Roberta
Parental misconceptions and even "demand" for unnecessary antibiotics were previously viewed as contributors to overuse of these agents. We conducted focus groups to explore the knowledge and attitudes surrounding common infections and antibiotic use in the current era of more judicious prescribing. Among diverse groups of parents, we found widespread use of home remedies and considerable concern regarding antibiotic resistance. Parents generally expressed the desire to use antibiotics only when necessary. There was appreciation of inherent error in the diagnosis of common infections, with most trust placed in providers with whom parents had long-standing relationships. While some parents had experience with "watchful waiting" for otitis media, there was little enthusiasm for this approach. While there may still be room for further education, it appears that parents have become more informed and sophisticated regarding appropriate uses of antibiotics. This has likely contributed to the declines seen in their use nationally.